Social Mobility of University Graduates: Which Pathways Lead Upwards? - N. Ya. Rosenfeld; V. A. Maltseva (Высшее образование в России)
At the present work using data from the longitudinal study of the National Research University Higher School of Economics “Trajectories in Education and Careers”, authors studied the relationship between the trajectories of university graduates and their chances for social mobility. Authors assessed, which characteristics of the path taken in education and the labor market by the age of 25 are associated with upward mobility. Using Blau and Duncan’s status attainment model, the movement from prescribed family status to attained status was analyzed. Two measures were used to assess status: subjective social status and financial status.Graduates by age 25 were most likely to have reproduced parental status, with the majority reproducing middle status, as measured by both subjective social status and financial status. The chances of upward mobility were significantly higher for university graduates who had had time to accumulate the most work experience by age 25. At the same time, the completion of a Master’s degree and prolonged studies, which do not allow for full-time employment, proved to be a risk factor for maintaining the prescribed status. Socio-economic and gender inequalities were also observed: male graduates and those from more educated families had significantly higher chances of upward social mobility. As a result, it was factors unrelated to education (work and socio-demographic factors), that proved to be significant for the success of graduates.